Acute and chronic effects of multivitamin/mineral supplementation on objective and subjective energy measures. - Dodd, F. L.; Kennedy, D. O.; Stevenson, E. J.; Veasey, R. C.; Walker, K.; Reed, S.; Jackson, P. A.; Haskell-Ramsay, C. F. (Nutrition & Metabolism, 2020)
Background: Vitamins and minerals play an essential role within many cellular processes including energy production and metabolism. Previously, supplementation with a multivitamin/mineral (MVM) for ≥28 days resulted in improvements to cognition and subjective state. We have also demonstrated shifts in metabolism during cognitively demanding tasks following MVM in females, both acutely and following 8-week supplementation. The current study aimed to assess these effects further in males and females using metabolically challenging exercise and cognitive tasks. Methods: The current randomised, placebo-controlled, parallel groups study investigated the effects of a MVM complex in 82 healthy young (18-35y) exercisers. Subjective ratings and substrate metabolism were assessed during 30 min each of increasingly effortful incremental exercise and demanding cognitive tasks. Assessments took place on acute study days following a single dose (Day 1) of MVM, containing 3 times recommended daily allowance of water-soluble vitamins plus CoQ10, and following 4-week supplementation (Day 28). Results: Energy expenditure (EE) was increased during cognitive tasks following MVM across Day 1 and Day 28, with greater effects in males. In males, MVM also increased carbohydrate oxidation and energy expenditure during exercise across Day 1 and Day 28. In females, mental tiredness was lower during exercise; increases in physical tiredness following 30 min of exercise were attenuated; and stress ratings following cognitive tasks were reduced following MVM. In males, MVM only lowered mental tiredness following 10 min of exercise. These effects were apparent irrespective of day, but effects on mental tiredness were greater on Day 28. Ferritin levels were also higher on Day 28 in those receiving MVM. Conclusion: These findings extend on existing knowledge, demonstrating increased carbohydrate oxidation and increased energy expenditure in males following MVM supplementation for the first time. Importantly, they show modulation of energy expenditure and subjective tiredness following a single dose, providing further evidence for acute effects of MVM. Differential effects in men and women suggest that sex may play an important role in the effects of MVM on energy metabolism and should be considered in future research. Trial registration: ClinicalTrials.gov, NCT03003442. Registered 22nd November 2016 – retrospectively registered